Motherhood and biosafety measures: Negotiating a compromise between traditional funeral customs and public health needs in Zimbabwe in the wake of COVID-19 - Mwandayi, Canisius (HTS teologiese studies, 2021)
Since the origins of humanity, motherhood has remained a central cog around which human societies revolve. With motherhood, it is not just the ability to give birth but the unbounded love, tolerance, patience and presence associated with a mother that keep motherhood unique. The onset of the ravaging coronavirus 2019 (COVID-19) pandemic and its variants have, however, seen a painful shift from some of these widely held expectations about motherhood. In Zimbabwe, the God-ordained Edenic bond is now under threat as mothers are now barred not only from griefly cuddling the deceased fruit of their womb but also from performing the last mourning rites on them. In line with biosafety measures, they are now to keep distance from them when they are laid to rest. Faced with such competing values, the paper advocates a compromise by arguing for safe and dignified burials as well as Mariopraxis in the midst of a seemingly defenceless situation. Employing synchronic methodologies namely close-reading and feminism, the paper interrogates the God-ordained Edenic bond which provides the basis to what motherhood is all about. The paper deliberately picks on Shona women on the grounds of acquaintance. Having been born to a Shona mother and raised within a Shona cultural environment, much of my ideas about Shona women will be drawn from interaction with my mother as well as with other Shona women. Desk research will be used to augment prior knowledge.Contribution: The research makes a unique contribution to women theology and the epidemics through proffering tangible ways to both the government and Shona mothers in dealing with emerging challenges associated with the COVID-19 pandemic. Given that women theology is a theology of hope, the article advocates Mariopraxis as it accords mothers the ability, through God, to face the pandemic with an assured hope that God is in control of everything.